The Early Modern Political Context to Spinoza”™s Bible Criticism - Morrow, Jeffrey (Revista de Filosofía)
The early modern political philosopher Benedict de Spinoza is often viewed as the father of the historical critical method for studying the Bible. Building upon the work of contemporaries, Spinoza constructed the methodological foundation upon which later historical criticism would build. This paper examines the political background of Spinoza”™s biblical criticism, thereby placing Spinoza”™s work in its sociohistorical context. The Thirty Years”™ War and the political turmoil in the Dutch Republic provide the proximate backdrop for Spinoza”™s political theory, and upon his biblical criticism.